2016
DOI: 10.18240/ijo.2016.04.09
|View full text |Cite
|
Sign up to set email alerts
|

Short term effects of small incision lenticule extraction surgery on corneal endothelium

Abstract: SMILE has no significant adverse effects on the corneal ECD and morphology during 1mo follow-up time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Wang et al 16 assessed the effects of small incision lenticule extraction (SMILE) surgery on the corneal endothelium at one day, one week, and one month postoperatively on 47 eyes who received SMILE surgery. The corneal endothelium was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 16 assessed the effects of small incision lenticule extraction (SMILE) surgery on the corneal endothelium at one day, one week, and one month postoperatively on 47 eyes who received SMILE surgery. The corneal endothelium was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 There are some reports that SMILE has no adverse effects on the corneal endothelium. 20 , 21 Kamiya et al 22 reported there was no significant difference in ECD after femtosecond laser-assisted keratoplasty (FLAK) and after conventional penetrating keratoplasty, even though energy was higher (300 nJ in FLAK vs 140 nJ in our study), spot distance was narrower (3.0 µm in FLAK vs 4.0 µm in our study), and depth of laser was deeper (vertically full thickness in FLAK vs minimal residual stromal bed 310 µm in our study). Park et al 23 reported a positive outcome after SMILE in a patient with posterior polymorphic corneal dystrophy, which has been described as a contraindication of LASIK 24 because of the risk of corneal decompensation.…”
Section: Discussionmentioning
confidence: 99%